The interaction between osteosarcoma and other cells in the bone microenvironment: From mechanism to clinical applications - Zeng, Jin; Peng, Yi; Wang, Dong; Ayesha, Khan; Chen, Shijie (Frontiers in Cell and Developmental Biology, 2023)
Osteosarcoma is a primary bone tumor with a high mortality rate. The event-free survival rate has not improved significantly in the past 30 years, which brings a heavy burden to patients and society. The high heterogeneity of osteosarcoma leads to the lack of specific targets and poor therapeutic effect. Tumor microenvironment is the focus of current research, and osteosarcoma is closely related to bone microenvironment. Many soluble factors and extracellular matrix secreted by many cells in the bone microenvironment have been shown to affect the occurrence, proliferation, invasion and metastasis of osteosarcoma through a variety of signaling pathways. Therefore, targeting other cells in the bone microenvironment may improve the prognosis of osteosarcoma. The mechanism by which osteosarcoma interacts with other cells in the bone microenvironment has been extensively investigated, but currently developed drugs targeting the bone microenvironment have poor efficacy. Therefore, we review the regulatory effects of major cells and physical and chemical properties in the bone microenvironment on osteosarcoma, focusing on their complex interactions, potential therapeutic strategies and clinical applications, to deepen our understanding of osteosarcoma and the bone microenvironment and provide reference for future treatment. Targeting other cells in the bone microenvironment may provide potential targets for the development of clinical drugs for osteosarcoma and may improve the prognosis of osteosarcoma.